Long-Term Effects of Maternal Deprivation on the Volume of Dopaminergic Nuclei and Number of Dopaminergic Neurons in Substantia Nigra and Ventral Tegmental Area in Rats - Kapor, Slobodan; Aksić, Milan; Puškaš, Laslo; Jukić, Marin; Poleksić, Joko; Milosavljević, Filip; Bjelica, Suncica; Filipović, Branislav (Frontiers in Neuroanatomy, 2020)
Early life adversities leave long lasting structural and functional concequences on the brain, which may persist later in life. Dopamine is a neurotransmitter, which is extremely important in mood and motor control. The aim of this study was to investigate the effect of maternal deprivation during the ninth postnatal day on the volume of dopaminergic nuclei and number of dopaminergic neurons in adolescence and adulthood. Maternally deprived and control Wistar rats were sacrificed at the postnatal day 35 or 60 and the dopaminergic neurons were stained in coronal histological sections of ventral midbrain with the tyrosine hydroxylase antibody. Volume of and number of dopaminergic neurons in the substantia nigra (SN) and ventral tegmental area (VTA) were analyzed in three representative coordinates. Maternal deprivation caused a weight loss at postnatal day 21 (weaning) and corticosterone blood level elevation at postnatal days 35 and 60 in the stressed compared to control rats. In maternally deprived animals, the volumes of SN and VTA were increased compared to controls. This increase is accompanied with an elevation in the number of dopaminergic neurons in both nuclei. Altogether, based on somatic and corticosterone level measurements, maternal deprivation represents a substantial adversity and the phenotype it causes in adulthood includes the increased volume of dopaminergic nuclei and number of dopaminergic neurons.